Efek Imunostimulan Ekstrak Etanol Kelopak Bunga Rosella - Wulandari, Dita; Puri, Putri Ratna; W, Ratna Kurnia; Nurkhasanah, . (Jurnal Farmasi Indonesia, 2014)
The aims of this study was to determine the immunostimulant potential ethanolic extract of roselle calyx through the proliferation of lymphocytes and phagocytosis ability of macrophages Balb/c mice in vitro. Dried calyx of roselle were extracted using 96% ethanol by maceration method is further polyphenols assay are qualitatively and quantitatively. Vitro test using with immunostimulants are seeing an increase in lymphocyte proliferation using the MTT method and phagocytosis activity macrophages with latex beads. Lymphocyte proliferation is expressed by the difference in absorbance values between treatment and control groups, where as the ability of phagocytosis is expressed as an index of phagocytosis and the SFA. Concentration of extract used was 10-1000 Î¼g/mL. Ethanolic extract of roselle calyc containing polyphenols with total polyphenol content (TPC) of 2.757%. Ethanol extract of roselle calyx enhanced immune response at low concentrations. Concentration Â of 100 Î¼g/mL is the optimal concentration that increased proliferation of lymphocytest. The highest index of phagocytosis and SFA are at concentrations of 150 Î¼g/mL and 250 Î¼g/mL. It can be concluded that ethanolic extract of roselle calyx has potential as immunostimulants.Keywords : roselle, immune response, macrophage phagocytosis, lymphocyte proliferation, immunostimulant.